PENGARUH KUALITAS LAYANAN TERHADAP KEPUASAN KONSUMEN PADA SWALAYAN SINAR BONE WIWIRANO KONAWE UTARA - Titin Anita Lestari (JOURNAL OF ADMINISTRATIVE AND SOCIAL SCIENCE, 2021)
Given the number of supermarkets (supermarket) which is located in the same area, then by itself would give birth to the fierce competition to seize visitors and buyers. Additionally the competition also came from some retailers in traditional markets and shops are scattered in the same area. Sinar Bone Supermarkets is one of the famous retail among some retail in the city of wiwirano Konawe utara. In the motion of daily operations, Sinar Bone Supermarkets as shopping centers provide a variety of different goods with different types, brands and sizes at varying price levels. Problem formulation, Based on the background outlined above, then the problem is: What is the quality of services that includes Tangible, Realibility, Responsiveness, Assurance, and Empathy effect on customer satisfaction in the Sinar Bone Supermarket wiwirano -konawe Utara .Objective, while the objectives of this research is to determine how much the quality of the services provided by Sinar Bone Supermarket. "Quality of service refers to judgments of customers about the core of this service and the service provider itself or the entire service organization, most people are now beginning to show demand towards service excellence, they are no longer just need a quality product, but they prefer to enjoy the convenience of service " The method used in this research is descriptive quantitative method in accordance with the purpose of the research presented in advance outlining the nature of the nature and looking for a systematic description of the facts under investigation From the discussion above results show that the performance of the services provided by the service provider is very influential on consumer satisfaction, the strategy adopted by a Sinar Bone Supermarket wiwirano -konawe Utara , especially in the service sector should be implemented properly.